OP0027 Characteristics of cytokines and changes in interleukin-17 levels in the synovial fluid of patients with ankylosing spondylitis on treatment with biologics. (12th June 2018) - Koo, B.S.; Jo, S.; Kwon, E.; Shin, J.H.; Kim, T.-H.
Abstract : Background: Biologic drugs targeting the inflammatory cytokines have been recommended in rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Yet, some patients require a change in treatment because an adequate response is not achieved. Objectives: The current study aimed to evaluate the levels of tumour necrosis factor alpha (TNF-α), interleukin (IL)−17, IL-23, and granulocyte-macrophage colony-stimulating factor (GM-CSF) in the joint fluid in patients with AS and RA and identify the important cytokines related with treatment-response. Methods: Synovial fluid was obtained from 18 patients with AS and 19 with RA who suffered from arthritis of the knee; and the levels of the cytokines were measured. The differences in their levels between patients with AS and RA, and between patients treated with and without biologics (biologics group and non-biologics group) were analysed. Results: TNF-α and GM-CSF levels in patients with AS were significantly lower than those in patients with RA (figure 1A, both p<0.01); however, IL-17 and IL-23 levels were not significantly different between the two groups. Furthermore, levels of IL-17 were markedly elevated in the biologics group compared with the non-biologics group in AS (figure 1B, p=0.04). However, in RA, there were no significant differences between the non-biologics and biologics group (figure 1C). Conclusions: In AS, IL-17 in synovial fluid is a good marker of non-response to biologics and may be a good target for non-responders to TNF inhibitor. Disclosure of Interest: None declared